RETRACTED: The Influence of Democratic Leadership Style, Physical Work Environment and Extrinsic Motivation on Employees’ Performance at PT. Mayasari Bakti Jakarta - Andri Wibowo; Herry Krisnandi; Kumba Digdowiseiso (Journal of Social Science, 2024)
This research aims to analyze the influence of democratic leadership style, physical work environment and extrinsic motivation on the performance of PT employees. Mayasari Bakti in Jakarta. This research data uses primary data in the form of a questionnaire to 110 respondents who work at PT. Mayasari Bakti using the multiple linear regression method which was processed using SPSS 17.0 software. From data that has met the validity test, reliability test and classical assumption test, the following regression equation is obtained: Y =5,823+ 0,316X1+0,252X2+0,257X3. Where are the employee performance decision variables (Y), democratic leadership style (X1), physical work environment (X2) and extrinsic motivation (X3). From the model feasibility test, it shows that the three independent variables studied are proven to have a positive effect on the dependent variable together. Through partial hypothesis testing, it can be seen that democratic leadership style, physical work environment and extrinsic motivation are proven to each have a positive influence on purchasing decisions, namely 55.60%, meaning that 55.60% of the dependent variable of employee performance can be explained by the independent variable, namely leadership style. democratic, physical work environment and extrinsic motivation. Meanwhile, the remaining 44.40% is explained by other variables that were not included in this research.